Report on professional attachment with Goh Hwee Cheng & Co. - Teo, Lay Chin. (2008)
The report gives the reader a first-hand account, albeit brief one, of the unique encounters of a vocational trainee at work. It also summarises, in the opinion of the writer, the effectiveness of the PA programme in achieving its desired objectives.